Reward preferences in South Africa’s media industry - Mark H.R. Bussin; Nokwanda N. Thabethe (SA Journal of Human Resource Management, 2018)
Orientation: Employee remuneration is a key driver of employee engagement and thus organisational performance. A thorough understanding of employee needs is essential to enable management to develop an equitable mix in reward strategy.